University students’ perspectives on open and distance learning (ODL) implementation amidst COVID-19 / Vloreen Nity Mathew and Ellen Chung - Mathew, Vloreen Nity; Chung, Ellen (Universiti Teknologi MARA, 2020)
Open and Distance Learning (ODL) has been implemented in universities around the world since decades ago. With COVID-19 pandemic, its implementation has been accelerated globally at an unprecedented speed and haste. Thus, the aim of this paper is to investigate the university students’ perspectives on ODL amidst COVID-19. By using the convenient sampling method, a total of 608 diploma and degree students throughout Malaysia have participated and shared their feedback on ODL implementation. The collected data covered their general feedback and what they enjoyed the most about ODL. Moreover, their recommendations on ODL implementation were analyzed by categorising the responses into different themes. The demographic data was summarized using descriptive analysis. A comparison between the diploma and the degree students’ perspectives is also discussed in the paper. The findings show that most students have positive perceptions on ODL implementation, where positive feedback and fun factors are highlighted by the respondents. Some students indicated that ODL should not be continued in the future semester, due to problems such as poor internet connection, budget constraints and time management issues. Recommendations on improvements for better ODL implementations in the near future are also provided. This study contributes to more effective ODL management by presenting the learners’ perspectives